Difficulties Facing Strategic and Educational Planning in the Ministry of Education in Palestine state - Alajjouri, Mahmoud Hoseen (Journal of Educational and Psychological Sciences, 2025)
The study aimed to explore the challenges facing strategic and educational planning, key transformations affecting it, and its impact on the quality of education and learners. It also examined the reference frameworks defining the Ministry of Education’s philosophy in adopting strategic management and planning, analyzed the strategic orientations adopted by the Ministry to support this approach, and identified obstacles hindering educational leaders in implementing these plans. The study employed a descriptive theoretical method based on documentary analysis of relevant literature and reports. Findings showed that strategic management and planning are among the main approaches adopted by the Palestinian Ministry of Education to reform the educational system, achieving tangible, nationally significant outcomes. However, implementation still faces challenges such as centralized decision-making, bureaucracy and duplication, unclear policies, shortage of qualified staff, limited involvement of key leaders, and external constraints imposed by the occupation that hinder the execution of many strategic plans.
Keywords: strategic and educational planning; Ministry of Education; Quality of education; Palestine state